Development of a 22q11DS psycho‐educational programme: exploration of the views, concerns and educational needs of parents caring for children or adolescents with 22q11DS in relation to mental health issues. (30th March 2017) - Alugo, T.; Malone, H.; Sheehan, A.; Coyne, I.; Lawlor, A.; McNicholas, F.
Abstract: Background: 22q11.2 deletion syndrome (22q11DS) is a multisystem genetic condition with a broad phenotype. It is associated with a high prevalence of depression and anxiety during childhood and increased risk of schizophrenia in adulthood. Despite this, studies report that families may receive inadequate information of mental health (MH) risks at diagnosis. Therefore, this study investigated parents' experiences of caring for a child with 22q11DS, investigated their knowledge regarding the risk of MH problems and assessed the need for a psycho‐educational programme. Methods: A qualitative design and purposeful sampling was utilized. Parents registered with the '22q11 Ireland' support group, and parents listed on the cleft palate database in a children's hospital in Ireland were invited to participate. Focus groups were held with 22 parents. Data were thematically analysed using Burnard's method of analysis. Results: Most parents had some knowledge of the relationship between 22q11DS and an increased risk of MH issues. Parents reported that MH information relating to 22q11DS was mainly obtained from 22q11DS conferences, the '22q11 Ireland' support group and the Internet. Parents expressed a need for information to prevent or cope with their child's MH issues. Parents suggested that the following topics would be quite useful in a psycho‐educational programme. These included information on the early warning signs of MH issues and guidance on when and how to tell the child about the condition and how to manage the child or young person's anxiety, obsessive behaviour or hearing voices. Conclusions: The findings indicated parental support for a psycho‐educational programme that would provide relevant, accurate and timely information on how to effectively care for a child with 22q11DS MH needs.